(The Used of Chitosan in Waste Water Treatment) - Sapto Hartanto, Eddy (Warta Industri Hasil Pertanian, 1997)
Chitosan is biopolymer Â that occur by treatment of chitin deactylation process, with strong alkali. Chitosan may be used in treating turbid matter in aqueous solution to help remove the turbid matter. Chitosan is used as a viscosity enhancer to settle solids suspended in liquids. Chitosan offers a good volume reduction of waste water, which is an essential requirement for water recovery and poilution prevention.